EV+A 1996 : Nous sommes tous des touristes : Limerick exhibition of Visual + Art 1996. - Blanqui, Auguste; Debray, Régis; Derrida, Jacques, 1930-2004; Flaubert, Gustave; Hinde, John; Lodge, David; Rimbaud, Arthur; Tortosa, Guy; Limerick City Gallery of Art (Limerick : Limerick City Gallery of Art, 1996)
Hains, Raymond ; Bernardini, Alain ; Karaïndras, Jason ; Doherty, Willie ; McCarthy, Caroline ; King, Brian ; Jauve, Valérie ; Niedermayr, Walter ; Kabakov, Ilya ; Dimitrijevic, Braco ; Tzaig, Uri ; O'Brien, Abigail ; Fontaine, Thierry ; Buren, Daniel ; Gilligan, Hilary ; Mahe, Gilles ; Graham, Paul ; Parr, Martin ; Hyber, Fabrice ; Gautel, Jakob ; Boltanski, Christian ; O'Connell, Maurice ; Philipsz, Susan ; Gette, Paul-Armand ; Somers, Gary ; Caro, Antonio ; Lavier, Bertrand ; Guilleminot, Marie-Ange ; Maher, Alice ; Rolfe, Nigel ; Nic Giolla Coda, Aine ; Daly, Dorothy Ann ; Hirschhorn, Thomas ; Prendergast, Kathy ; Moulène, Jean-Luc ; Clément, Gilles ; Leccia, Ange ; Minnis, Michael ; MacLennan, Alastair ; Cross, Dorothy ; Weiner, Lawrence ; Negro, Marylène ; Parr, Martin
Engels
Frans
EV+A 1996 : Nous sommes tous des touristes, Limerick City Gallery of Art Limerick, 09.03 - 05.04.1996
kunstcatalogus